Combination of DNA Molecular Biomarkers in the Prediction of Critical Illness Outcome - V. M. Pisarev; A. G. Chumachenko; A. D. Filev; E. S. Ershova; S. V. Kostyuk; N. N. Veiko; E. K. Grigoriev; E. V. Elysina; R. A. Cherpakov; A. V. Tutelyan (Общая реаниматология)
Purpose: to determine the informative value of the prediction of mortality of patients with sepsis using a combination of candidate markers — the quantitative content of circulating cell-free DNA (cfDNA) in plasma and allelic variants of TLR9 gene encoding-cellular recognition receptor TLR9 for DNA fragments.Materials and methods. The study included patients from five ICU of 4 four hospitals (n=156). The patients were divided into 2 groups: (1) with sepsis (based on SEPSIS-3, 2016, criteria), (n=81) and with acute cerebrovascular event (n=75). CfDNA was isolated from patient’s blood plasma using organic solvents and its concentration was established by a spectrophotometer using fluorescent intercalating agent SYBR Green binding DNA with high affinity. Genotyping of rs352162 allele variants of TLR9 gene was carried out with the help of polymerase chain reaction using tetraprimers followed by separation of products via electrophoresis and their visualization. The cfDNA concentrations were compared in patients differ in TLR9 rs352162 genotypes and outcome was predicted in 30 days after hospitalization using the ROC analysis.Results. As regards the cfDNA content, there was no significant difference between patients with sepsis (subgroups with abdominal or non-abdominal sepsis) from two different hospitals, and cfDNA concentration in groups of patients was not associated with the source of primary infection, which allowed increasing group size by pooling up the data. Pooled data have shown that the sensitivity and specificity of the lethal outcome prediction based on the cfDNA content depends on the genotype: in homozygotic patients withg TLR9 rs352162 CC genotype, the AUC was significantly higher than in the alternative group of patients with TLR9 rs352162 CT and TT genotypes.Conclusion. The data we obtained suggest high informative value of establishing the genetic polymorphism of TLR9 as complimentary to determining the cfDNA concentration and may demonstrate potential usefulness of selecting patients according to their TLR9 genotype for investigations of the clinical effect of targeted drugs inhibiting interaction of cfDNA with receptor TLR9.